4D Cell‐Condensate Bioprinting. Issue 36 (16th August 2022) - Ding, Aixiang; Lee, Sang Jin; Tang, Rui; Gasvoda, Kaelyn L.; He, Felicia; Alsberg, Eben
Abstract: 4D bioprinting techniques that facilitate formation of shape‐changing scaffold‐free cell condensates with prescribed geometries have yet been demonstrated. Here, a simple 4D bioprinting approach is presented that enables formation of a shape‐morphing cell condensate‐laden bilayer system. The strategy produces scaffold‐free cell condensates which morph over time into predefined complex shapes. Cell condensate‐laden bilayers with specific geometries are readily fabricated by bioprinting technologies. The bilayers have tunable deformability and microgel (MG) degradation, enabling controllable morphological transformations and on‐demand liberation of deformed cell condensates. With this system, large cell condensate‐laden constructs with various complex shapes are obtained. As a proof‐of‐concept study, the formation of the letter "C"‐ and helix‐shaped robust cartilage‐like tissues differentiated from human mesenchymal stem cells (hMSCs) is demonstrated. This system brings about a versatile 4D bioprinting platform idea that is anticipated to broaden and facilitate the applications of cell condensation‐based 4D bioprinting. Abstract : A 4D bioprinting strategy that enables the construction of complex scaffold‐free cell condensates through predefined shape transformations is reported. Cell condensates with diverse geometries can be designed to undergo preprogrammed deformations over time. With this system, complex tissues are engineered through controlled shape morphing and tissue maturation. This 4D bioprinting strategy opens an avenue for scaffold‐free 4D tissue engineering.